Meditation and Yoga in pregnancy: maternal and fetal impact - Mehta, Sumita; Grover, Anshul; Kale, Ekta; Nanda, Pratibha; Mehta, Akshaj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Yoga is a practice which amalgamates the emotional, mental, physical and spiritual aspects of the human body through physical postures(asanas), breathing exercises (pranayama), concentration and meditation (dharana and dhyana). Evaluation of databases suggests a positive role of yoga in pregnancies associated with depression, anxiety and lumbosacral pain and also in reducing antepartum complications and pain score during labor. These beneficial effects of yoga are suggested but more systematic researches are required to validate it. With the background of above researches, we undertook the study to evaluate the effect of prenatal yoga and meditation on maternal and fetal outcomes. Aim of the study was to determine the effect of antenatal meditation and yoga on obstetric and fetal outcome. Methods: This was a prospective randomized trial conducted in the antenatal OPD of the institute. Sixty primigravida women with low risk pregnancy between 18 to 26 weeks gestation were included in the trial.They were randomly divided into two equal groups; interventional group underwent meditation and yoga sessions of 30 minutes twice in a week till delivery. Obstetric outcomes including gestational age, antepartum and intrapartum complications, cord blood cortisol levels at delivery and neonatal outcomes were recorded. Results: Thirteen women went post-dated as compared to 3 in the interventional group which was statistically significant (p=0.0003). APGAR scores of neonates in the interventional group showed a highly significant improvement with p=0.0013 as compared to the control group. Cord blood cortisol levels were higher than 10 ng/ml in 16 women in the control group compared to 7 in the group who performed yoga and meditation with p=0.01. NICU admissions were significantly more (p=0.002) in the control group. Conclusions: Meditation and yoga during pregnancy improves maternal and neonatal outcomes.